2004
DOI: 10.1074/jbc.m311806200
|View full text |Cite
|
Sign up to set email alerts
|

Stopped-flow Fluorescence Analysis of the Conformational Changes in the GroEL Apical Domain

Abstract: GroEL undergoes numerous conformational alterations in the course of facilitating the folding of various proteins, and the specific movements of the GroEL apical domain are of particular importance in the molecular mechanism. In order to monitor in detail the numerous movements of the GroEL apical domain, we have constructed a mutant chaperonin (GroEL R231W) with wild type-like function and a fluorescent probe introduced into the apical domain. By monitoring the tryptophan fluorescence changes of GroEL R231W u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
33
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 31 publications
5
33
0
Order By: Relevance
“…An additional kinetic study from Taniguchi et al (2004) monitored a tryptophan substituted at position 231 at one edge of the face of the apical domain, both in GroEL and SR1, observing the same results. These two studies thus offer parallel views of the steps taking place during the binding-to-folding transition of a ring.…”
Section: Fluorescence Changes Of Groel W485 and W231 As Monitors Of Ssupporting
confidence: 58%
“…An additional kinetic study from Taniguchi et al (2004) monitored a tryptophan substituted at position 231 at one edge of the face of the apical domain, both in GroEL and SR1, observing the same results. These two studies thus offer parallel views of the steps taking place during the binding-to-folding transition of a ring.…”
Section: Fluorescence Changes Of Groel W485 and W231 As Monitors Of Ssupporting
confidence: 58%
“…When ATP binds rapidly to GroEL, does this cause significant adjustment in the apical polypeptide binding domains on the same rapid time scale, or are the apical changes in response to ATP binding relatively slow, such that the effects of ATP binding must be considered to be occurring at a later time? The earlier study of R231W had already indicated that apical effects occurred rapidly with that mutant (17). In the present study as well, a fluorescent probe on the outside aspect of the apical domains, remote from the ATP binding site on the inside of the cylinder (GroEL E315C in a cysteine-zero background labeled with OG), showed a rapid change in fluorescence intensity, on the same time scale as ATP binding.…”
Section: Equally Rapid Fluorescence Change On Atp Binding To Open Tramentioning
confidence: 48%
“…Moreover, polypeptide association with apical domains that have been mobilized could potentially affect the efficiency of binding. Such an order of addition with ATP binding before substrate protein seems plausible considering previous rate measurements that indicate, on one hand, rapid binding of ATP to unliganded GroEL (16)(17)(18) and, on the other hand, relatively slow binding of such substrate proteins as MDH and Rubisco to unoccupied GroEL or to asymmetrical GroEL/GroES/ADP complexes, respectively (19,20). Here, we have systematically investigated the relative rates of arrival of ATP and substrate protein ligands to both unliganded GroEL and asymmetrical GroEL/GroES/ADP complexes and find that the physiological order of arrival entails rapid ATP binding, producing nearly as rapid apical domain movement, followed by slower binding of substrate protein.…”
mentioning
confidence: 99%
See 2 more Smart Citations